2018
DOI: 10.4172/1948-5964.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Inhibits the Replication of Zika Virus

Abstract: Background: The emergence of Zika virus (ZIKV) is associated to dramatic complications in fetuses and neonates. As there is no vaccine and no drug to prevent and treat ZIKV infections, there is an urgent need to have active drugs against ZIKV that can be used during pregnancy. Large screening strategies suggested that azithromycin (AZ) has an in vitro activity against ZIKV, we provide additional data supporting this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 45 publications
2
100
0
9
Order By: Relevance
“…Repositioning of drugs for use as antiviral treatments is a critical need [1]. It is commonly very badly perceived by virologists, as we experienced when reporting the effectiveness of azithromycin for Zika virus [2]. A response has come from China to the respiratory disease caused by the new coronavirus (SARS-CoV-2) that emerged in December 2019 in this country.…”
mentioning
confidence: 99%
“…Repositioning of drugs for use as antiviral treatments is a critical need [1]. It is commonly very badly perceived by virologists, as we experienced when reporting the effectiveness of azithromycin for Zika virus [2]. A response has come from China to the respiratory disease caused by the new coronavirus (SARS-CoV-2) that emerged in December 2019 in this country.…”
mentioning
confidence: 99%
“…Azithromycin has been displayed an antiviral property against Zika and Ebola virus in vitro (Bosseboeuf et al, 2018;Madrid et al, 2015;Retallack et al, 2016). It can prevent severe respiratory tract infection in the case of viral infected patients (Bacharier et al, 2015).…”
Section: Trial Test Of the Fda-approved Drugs For Covid-19 Patientsmentioning
confidence: 99%
“…In vitro studies have shown that azithromycin is active against Zika and Ebola viruses, [18][19][20] and is able to prevent severe respiratory tract infections when administrated to patients suffering viral infection [12] However, the efficacy of azithromycin in combination with hydroxychloroquine in the treatment of COVID-19 patients has not been confirmed yet [21,22], and more studies are needed to further investigate its clinical effects. In light of the current shift of dental services towards the provision of emergency treatment only, and the possible increase in antibiotic prescriptions for severe orofacial infections, the use of azithromycin in dentistry should be monitored, especially that its use in dental practice as a favorable antibiotic is reported in countries with a high toll of COVID-19 infections.…”
Section: Azithromycinmentioning
confidence: 99%